Human Resource Procurement in Pesantren? Insight from Pesantren Sirojuth Tholibin - Sholihah, Baqiyatush (Nadwa: Jurnal Pendidikan Islam, 2020)
Human resource procurement is one of the essential stages of organizational decision-making. The scope of procurement consists of planning, recruitment, selection, placement, and orientation of new personnel. Human resources studied in this research are situated in Pesantren comprising of the committee or board; teachers of kitab kuning (classical Arabic Islamic textbook) either with sorogan or bandongan methods; teachers of reciting and memorizing Al-Qurâ€™an; persons in charge of media such as website, Facebook, Twitter, Instagram, YouTube, magazines, and newsletters of Sirojuth Tholibin both. Sirojuth Tholibin commonly used a bottom-up approach in human resources planning.Â  As a part of the planning process, The institution usually combines unstructured interview and observation methods in job analysis. In recruitment and selection, Sirojuth Tholibin pays more attention to behavioral competencies over technical competencies. Recruitment of committee and teachers usually carried out through the employee referral method. Those recruited and selected are recommendations from previous administrators who understand the background of potential candidates. The placement of new human resources is made based on their respective competencies. Orientation is the responsibility of each department, and the duration is according to the speed of each new individual in capturing new knowledge related to their jobs. The weakness of human resources procurement in Sirojuth Tholibin has no formal written job description and job specification. There is also a lack of management information systems of human resource procurement.